PENDIDIKAN MORAL DALAM NOVEL KUNCUP BERSERI KARYA N.H. DINI: PERSPEKTIF SOSIOLOGI SASTRA DAN PENERAPANNYA DALAM PEMBELAJARAN - FAUZIAH, QODARIANA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research aims to describe: (1) the sociohistorical context of the author of the novel Kuncup Berseri; (2) the moral educational value of the novel; (3) application of research results from the novel Kuncup Berseri as an option for literature teaching materials at MTs. This research is a qualitative descriptive study that uses a literary sociology approach. The data source used comes from the novel Kuncup Berseri written by Nh. Early. The research data includes the sociohistorical background of the author of the novel Kuncup Berseri as well as the moral educational values contained in the work. Information sources involve data obtained directly (primary) and data obtained through other sources (secondary). Data collection was carried out through library techniques, which involved reading the novel being analyzed, recording data related to moral educational values, and classifying the data according to the needs of the analysis. The validity of the data is tested through theoretical triangulation by conducting research on the same topic and collecting several documents or theories that are relevant to the research object. Sample determination was carried out using a purposive sampling method or a determined sample. Data were analyzed by applying the dialectical reading method. The research results show that the novel Kuncup Berseri is one of the works of Nh. Dini, apart from telling personal memories, also explains various events and traditions of the community where she grew up, namely Javanese culture. The story structures in the novel Kuncup Berseri are related to each other. The values of moral education in the form of human relationships with themselves, human relationships with other people, human relationships with God, as well as moral values of Javanese culture are found in this novel. The results of the research can be implemented as an alternative literature teaching material in class IX MTs/SMP in the Basic Competency of finding elements of the fiction books that are read. ABSTRAKPenelitian ini bertujuan untuk menggambarkan: (1) konteks sosiohistoris dari pengarang novel Kuncup Berseri; (2) nilai pendidikan moral novel; (3) penerapan hasil penelitian dari novel Kuncup Berseri sebagai opsi materi pengajaran sastra di MTs. Penelitian ini adalah studi deskriptif kualitatif yang menggunakan pendekatan sosiologi sastra. Sumber data yang digunakan berasal dari karya novel Kuncup Berseri yang ditulis oleh Nh. Dini. Data penelitian mencakup latar sosiohistori pengarang novel Kuncup Berseri serta nilai-nilai pendidikan moral yang termuat dalam karya tersebut. Sumber informasi melibatkan data yang didapat secara langsung (primer) dan data yang diperoleh melalui sumber lain (sekunder). Pengumpulan data dilakukan melalui teknik pustaka, yang melibatkan membaca novel yang sedang dianalisis, mencatat data yang berkaitan dengan nilai-nilai pendidikan moral, dan mengklasifikasikan data sesuai dengan kebutuhan analisis. Validitas data diuji melalui triangulasi teori dengan melakukan penelitian pada topik yang sama dan mengumpulkan beberapa dokumen atau teori yang relevan dengan objek penelitian. Penentuan sampel dilakukan dengan metode purposive sampling atau sampel yang ditentukan. Data dianalisi dengan menerapkan metode pembacaan dialektik. Hasil penelitian menunjukkan bahwa novel Kuncup Berseri adalah salah satu karya Nh. Dini yang selain mengisahkan kenangan pribadi, juga membeberkan berbagai kejadian dan tradisi masyarakat tempat dia dibesarkan, yaitu budaya Jawa. Struktur cerita dalam novel Kuncup Berseri saling terkait satu sama lain. Nilai-nilai pendidikan moral yang berupa hubungan manusia dengan diri sendiri, hubungan manusia dengan orang lain, hubungan manusia dengan Tuhan, serta nilai moral budaya Jawa terdapat dalam novel ini. Hasil penelitian dapat diimplemantasikan sebagai alternatif bahan ajar sastra di kelas IX MTs/SMP dalam Kompetensi Dasar menemukan unsur-unsur buku fiksi yang dibaca.